775 views
0 votes
HELP

F=3
J=-3
I=2
G=0
H=0
0(0(2(-3(3(1)))))=0
^^i think that is right but I need to show my work and explain

HELP F=3 J=-3 I=2 G=0 H=0 0(0(2(-3(3(1)))))=0 ^^i think that is right but I need to-example-1

1 Answer

6 votes

f is a function defined by

{(-3, 1), (-2, 2), (-1, -3), (0, -1), (1, 3), (2, -2), (3, 0)}

so f (1) = 3. Then

h (g (i (j (f (1))))) = h (g (i (j (3))))

j is defined by

{(-3, 0), (-2, 1), (-1, 2), (0, -1), (1, -2), (2, 3), (3, -3)}

so j (3) = -3, and

h (g (i (j (f (1))))) = h (g (i (-3)))

And so on. Next you have i (-3) = 2, then g (2) = 0, and finally, h (0) = 0, so your answer is correct.

User Sudharsun
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.